Scope and contradictions of the policies of “formalization” of street vendors in the city of Lima - Vildoso Chirinos, Carmen (Sociología del Trabajo, 2024)
The study aims to show the complexity of the proposed transition from informality to formality. The case of street vendors is studied, who are characterized as informal in several senses, including the dimension of employment and that of occupants of public spaces. It analyzes the reality of street vendors in the city of Lima and the policies deployed by municipal administrations, especially in the Historic Center and surrounding areas over the last decades. Academic literature on this sector has been reviewed, as well as archives and documents of the municipality of Lima; likewise, field observation work has been carried out during the years 2021-2023. We identified the limits of municipal policies aimed at getting street vendors to leave the streets, eventually setting as an objective to achieve their formalization..